2010
DOI: 10.1377/hlthaff.2010.0840
|View full text |Cite
|
Sign up to set email alerts
|

How Geisinger’s Advanced Medical Home Model Argues The Case For Rapid-Cycle Innovation

Abstract: The Patient Protection and Affordable Care Act of 2010 provides for a number of major payment and delivery system initiatives. These potential changes need to be tested, scaled, and adapted with an urgency not evident in previous demonstration projects of the Centers for Medicare and Medicaid Services. We discuss lessons learned from our iterative tests of care reengineering at Geisinger--specifically, through our advanced medical home model, ProvenHealth Navigator, and the way we continuously modified the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 8 publications
(8 reference statements)
1
59
0
1
Order By: Relevance
“…17,18 Thus, the primary care practice plays the central role in the delivery of high value care, and benefits directly from additional payments.…”
Section: Unit Of Organizationmentioning
confidence: 99%
“…17,18 Thus, the primary care practice plays the central role in the delivery of high value care, and benefits directly from additional payments.…”
Section: Unit Of Organizationmentioning
confidence: 99%
“…14,15 Others have looked at fulfilling this role in the outpatient setting. 16,17 A recent systematic review of primary care clinic-based postdischarge phone calls showed no impact on readmission rates, but only 3 studies were included. 18 Health plan-initiated telephone calls to plan members after hospital discharge reported a 22% reduction in readmissions.…”
Section: After Hospital Dischargementioning
confidence: 99%
“…[8][9][10] In fact, the complexity underlying achievement of medical homes may be out of reach of many PC practices, 11 especially those without electronic health records, data systems, access to care managers, structured practice facilitation, and other key elements. [12][13][14][15] Findings from widely publicized medical home efforts, such as those at Geisinger, Intermountain and Group Health, suggest early provider burnout and significant challenges in operationalizing the tenets of PCMH in diverse settings, yet have nonetheless managed to accomplish important process and outcome changes. 16 We address these questions in the Veterans Health Administration (VA), the largest integrated healthcare delivery system in the U.S., with hospital-based and freestanding PC clinics spanning all 50 U.S. states and several territories.…”
Section: Introductionmentioning
confidence: 99%